การใช้หลอดแอลอีดีเป็นแหล่งให้แสงสำหรับชุดปลูกพืชไฮโดรโปนิกส์ - สุทธิดา มณีเมือง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Light-emitting Diode or LED is one of semiconductor which is commonly used for hydroponics plant production in greenhouse as light source. LED become to be used in multitasking lighting for plant production due to many advantages over the early light source including low energy consumption and minimum heating compared with conventional lighting such as fluorescent lamp. Light emitted from LED have wavelength specificity are suitable for photosynthesis and plant production. This recent study is aimed to design and produce LED as light source for hydroponics Red Oak and Green Oak productions in greenhouse which are controlled air temperature and relative humidity. Greenhouse system consisted of hydroponics kits with dimension of width, length and height are 60 120 and 87 cm by order. The average air temperature and relative humidity in hydroponics greenhouse were controlled throughout the experiment at 29.0 oC and 60.7%, respectively. Design and produce the LEDs with radial arrays which have high level of illuminance and constant brightness area of plants canopy. The fifty of LEDs are mounted on a square plate with dimension of 30 cm with circular arrangement at 5.0 12.2 19.4 and 27.0 cm. The dispersion radius of light emitted from LEDs at 30 cm of test plane is 17 cm covered the plant production areas. Thus, This radial array of 50 LEDs can be used as a basic designed arrangement for the mixing of 454 nm blue and 660 nm red LED. The blue-red combined LEDs with illuminace of 1,390 ± 18 Lux were tested by varying the mixing ratio and set at the level of 30 cm above plant canopy as light sources. It was found that the appearance of Red Oak and Green Oak grown under blue-red combined LED with the mixing ratio of 30:70 based on its illuminance were completely normal closed to those grown under sunlight. The average of total fresh weight observed in Red Oak and Green Oak were 9.6252 and 12.59 g which were higher than Red Oak and Green Oak grown under fluorescent lamp 100 and 120%, respectively. Using of blue-red combined LED with the mixing ratio of 30:70 as a light source for hydroponic both of Red Oak and Green Oak production can be reduced the energy consumption up to 77% compared to fluorescent lamp.